Proces realizacji zamówienia indywidualnego (na przykładzie firmy produkującej studnie szczelne) - Kaczmarek-Kalisz, Dominika (Individual Order Completion Process (Based on the Example of a Company Producing Concrete Manholes), 2009)
In the article, an analysis and evaluation of the individual order completion process in the production plant (which operates in concrete manholes production business) were presented. "Bottle-necks" that appeared in the examined process were identified and incidental improvement possibilities, solving identified information, organizational, technical and personnel problems were presented. More attention was paid to permanent organizational solutions, proposing implementation of process management concept and to imposition of, so-called, income generating centres on the analyzed process.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 170-177